Then David Wrote a Letter (2 Sam. 11:14) - He Himself or Was It His Secretary? A Study of the Criteria for Handling the ‘Semantic Causative’ - Käser, Andreas (Tyndale bulletin, 2014)
One often speaks of important people as if they did everything on their own. ‘Caesar beat the Gauls’, thus reads a verse in a poem by Bertolt Brecht. In the following line he makes the point: ‘Did he not even have a cook with him?’ This way of speaking about kings and lords, rulers and commanders, is a very common literary device used not only in many ancient but also in contemporary languages. In speech it is usually used unconsciously—and even decoded unconsciously. But it is at least noticeable, because sometimes the translators of the Old Testament use a causative in its place. As a result of this usually unnoticed decoding, this characteristic has rarely been explicitly described as a literary phenomenon. The only exception I know of is to be found in Hermann Menge’s book about Latin syntax and stylistics, where it is referred to as a ‘causative active’. Because it is grammatically an ‘active’ voice which is to be semantically decoded functionally as a ‘causative’, I would like to suggest calling this literary device a ‘semantic causative’. Now, if this ‘semantic causative’ is a common form used when speaking about important people, it raises the question: are there criteria which enable us to determine which of the acts are carried out by themselves and which are delegated to others. In my opinion there are indeed certain criteria which can be used to exclude the one or other scenario, but oftentimes a grey area of uncertainty seems to remain. So, did David write this letter himself or was it written by a secretary? In the following I intend to investigate the question of whether a definite answer can be found.